STUDENTS’ PARTICIPATION IN LEARNING ARGUMENTATIVE WRITING THROUGH WRITING WORKSHOP - Ardianti, Triubaida Maya; Bharati, Dwi Anggani L. (Universitas Negeri Semarang, 2016)
The present study was a part of a larger research. It aimed at investigating the dynamics of the students’ participation in learning argumentative writing through writing workshop. The present study took place in a natural science class consisting of 32 eleventh graders for 6 weeks. I employed questionnaire and observation to gather data, and collected the students’ works to strengthen the data analysis. The data yielded a result that the students’ participation in establishing oral and written argumentative discourse improved throughout learning cycles. In this circumstance, the students produced more talk in arguing over an issue, and became more active in writing collaboratively with their peers. Consequently, they got better in articulating their thoughts in written argumentation. It was affirmed by the improvements on the mean of the students’ argumentative writing and the quality of their argumentation.